Income and Fertility of Female College Graduates in the United States - Zhengyu Cai; John V. Winters (Institute of Labor Economics (IZA), 2024)
Fertility rates have fallen below replacement levels in many economies. We examine the relationship between female incomes and fertility for college graduates in the United States. Female income is likely endogenous to fertility, and candidate instrumental variables are likely imperfect. We use the Nevo and Rosen (2012) imperfect instrumental variable procedure to estimate two-sided bounds for the effect of female income on fertility. The effect of female income on fertility is unambiguously negative and non-trivial, but the magnitude is relatively small. Our results suggest that the recent fertility slowdown in the U.S. is not primarily due to higher female incomes.
Keywords: J13; J16; 330; fertility; children; motherhood; female income